Depiction of Chamunda and a deity below the image of Chamunda - Temples of India Project Team (Jio Institute, 2024)
One can notice the Chamunda imagery, on the south wall of the garbhagriha, with an emaciated body, dried and saggy breasts and a sunken belly. She has a jatamukuta and is adorned with ornaments. It is worth noticing that she is wearing a snake as her waist belt and carrying different astras and a bowl. Beneath the bhadra, on the vedibandha, a deity is shown seated on a pedestal, covered in vermilion which shows that the deity is worshipped regularly.